2010
DOI: 10.1111/j.1440-1797.2010.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Nestin is a novel marker for renal tubulointerstitial injury in immunoglobulin A nephropathy

Abstract: Nestin expression is associated with tubulointerstitial injury and predicts renal prognosis in IgA nephropathy. Nestin could be a new marker for peritubular endothelial cell injury and tubulointerstitial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…By using samples of patients with crescentic glomerulonephritis, Thorner et al [33] found that nestin was detected in more than 50% of the crescents in the renal species. In the study by Tomioka et al [34], expression of nestin was increased in the tubulointerstitium of patients with IgA nephropathy, whilst in normal kidney it was hardly detected in the tubulointerstitium. A further study demonstrated that peritubular endothelial cells and tubulointerstitial myofibroblasts expressed nestin during the progression of tubulointerstitial injury and nestin expression was associated with deterioration of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…By using samples of patients with crescentic glomerulonephritis, Thorner et al [33] found that nestin was detected in more than 50% of the crescents in the renal species. In the study by Tomioka et al [34], expression of nestin was increased in the tubulointerstitium of patients with IgA nephropathy, whilst in normal kidney it was hardly detected in the tubulointerstitium. A further study demonstrated that peritubular endothelial cells and tubulointerstitial myofibroblasts expressed nestin during the progression of tubulointerstitial injury and nestin expression was associated with deterioration of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the number of nestin/smooth muscle ␣-actin Ï© cells identified in the damaged kidney positively correlated with fibrosis (46). In 2010, Tomioka and colleagues (52) reported an analogous paradigm in the injured human kidney secondary to immunoglobulin A nephropathy as nestin was detected in a subpopulation of smooth muscle ␣-actin Ï© myofibroblasts. Tomioka et al (52) further demonstrated that nestin expression positively correlated with tubulointerstitial fibrosis, and patients with higher levels of the intermediate filament protein were associated with a significant worsening of renal function.…”
Section: Nestin Expression In Endothelial Cells and Myofibroblastsmentioning
confidence: 99%
“…In 2010, Tomioka and colleagues (52) reported an analogous paradigm in the injured human kidney secondary to immunoglobulin A nephropathy as nestin was detected in a subpopulation of smooth muscle ␣-actin Ï© myofibroblasts. Tomioka et al (52) further demonstrated that nestin expression positively correlated with tubulointerstitial fibrosis, and patients with higher levels of the intermediate filament protein were associated with a significant worsening of renal function. Therefore, injury to the heart and kidney is associated with the appearance of a subpopulation of nestin/smooth muscle ␣-actin Ï© myofibroblasts.…”
Section: Nestin Expression In Endothelial Cells and Myofibroblastsmentioning
confidence: 99%
“…These data suggest that nestin may play an important role in maintaining the normal morphology and function of podocytes. Further, several studies have shown that nestin expression is induced in other types of renal parenchymal cells following renal injury, suggesting the potential role of nestin in repairing kidney damage [12,14,15,16,17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%